Educação permanente nas políticas de saúde e assistência social no contexto da precarização do trabalho de assistentes sociais - Costa, Marcia de Assis (2016)
This thesis analyzes the continuing education of social workers inserted in the health and social care policies, at the levels of Basic Care and Primary Social Protection, questioning how the changes resulting from the processes of restructuring the Public structure have an impact on working conditions and require continued improvement for qualified professional responses. Regarding the object of this study, it is considered that Continued Education is a dimension of the work process and professional qualificiation, which requires political direction for the consolidation of the ethical-political project of Social Work. Also the understanding on how continued education focused in meeting the demands of the labor market is confronted by conceptions advocated in the policies of the areas studied and the set CFESS / CRESS IS sought in this paper. For the unveiling of the thesis subject, bibliographical and documentary research in theoretical productions in the areas of Social Services, Education and Sociology have been done and the categories Work and Education in the dialogue with professional work in the State public sphere have been probed. To collect data, qualitative research was conducted in the form of interviews based on semi-structured script, with 21 social workers (11 from Healthy Services and 10 from Social Care Services), working in different services of Basic Health and Social Care Reference Centers (CRAS). The analysis pointed out the close relationship between the current debate on Continued Education and the employability speech, beyond the poor knowledge of interviewees on the permanent education policy in the areas they operate, in a context of managerial and productionist management, which contributes to the intensification and precariousness of social workers working. The conclusion emphasizes the importance of the political dimension of work and training, to guarantee that the professional qualification is in line with the ethicalpolitical project of Social Work